A composite prepared from MoS2 quantum dots and silver nanoparticles and stimulated by mercury(II) is a robust oxidase mimetic for use in visual determination of cysteine - Ojha R.P.; Mishra R.; Singh P.; Nirala N.R.; Prakash R. (My University, 2025)
MoS2 quantum dots were hydrothermally synthesized and utilized for the formation and stabilization of a nanocomposite with silver nanoparticles (AgNPs) in a single step. This composite was characterized by transmission electron microscopy and zeta potential measurements. It is found that this nanohybrid can be stimulated by mercury(II) ion and then exhibits excellent oxidase mimicking activity. The oxidase-like activity is demonstrated by the oxidation of 3,3′,5,5′-tetramethylbenzidine by H2O2 that leads to the formation of a blue product. An assay was developed for determination of cysteine (Cys) at ultra-trace level because Cys inhibits the activity of the nanozyme via interaction with Hg(II). The Cys assay, best performed at a wavelength of 652 nm, works in the 1–100 μM concentration range and has a 0.82 μM detection limit. In addition, a portable Cys test kit is described that was applied to the determination of Cys in serum samples. The resulting colorations were compared with color chat wheel. The method is simple, rapid, cost-effective, and sensitive. [Figure not available: see fulltext.]. © 2019, Springer-Verlag GmbH Austria, part of Springer Nature.